KNOWLEDGE ECONOMY AND THE FUTURE OF HUMAN JOBS (World Economics and Finance Bulletin, 2022)
The current phase of global economic development is characterized by a gradual increase in the level of thought and the transition to a knowledgebased economy and defined as "production and services are based on knowledge-intensive activities". Innovation, education, knowledge and creativity are the most important feature of the knowledge economy. The lack of transparency, accountability, cronyism, youth unemployment, weak economic sector, political violence, lack of investment in human capital, lack of research and development spending and training of the greatest challenges to the issue of the knowledge economy in the Arab world are significantly reduced, but some Arab countries, particularly the Gulf states, are beginning to take a step towards a knowledge-based economy. The results of this research show that future jobs will change radically and robots will take over most jobs by 2025 and the machines will work more than today.
Keywords: Knowledge; Human; Economy; Jobs